An active geophone with an adjustable electromagnetic negative stiffness for low-frequency vibration measurement. (1st October 2022) - Ding, Jiheng; Wang, Youyong; Wang, Min; Sun, Yi; Peng, Yan; Luo, Jun; Pu, Huayan
Highlights: Active geophone with adjustable electromagnetic negative stiffness mechanism. Electromagnetic mechanism provides a linear negative stiffness in several millimeters. Initial misalignment and nonlinearity reveal the necessity of active control. Abstract: The low-frequency performance of an active vibration isolation system depends on the low-frequency measurement ability of inertial sensors such as geophones. Reducing the stiffness of the interior mechanical spring may serve as an effective way to improve the low-frequency performance of a geophone. But unfortunately, this approach may lead to a nonlinear response and a stability problem. This paper develops an active geophone with an adjustable electromagnetic negative stiffness (AENS). The AENS of the proposed geophone consists of two pairs of magnet rings and coil winds and adopts a concentric nested configuration. The AENS neutralizes the positive stiffness of mechanical spring and provides a low linear composite stiffness in a stroke range of ± 4.4 mm without affecting the high-frequencies stability of the active geophone. Besides, the "drift" phenomenon caused by an initial installation misalignment of the AENS is discussed. The analyzed result shows that once the misalignment happens, the deviation from the initial position will aggravate further. Therefore, by combining the AENS with active control of a drift suppression and a force-balance, the nonlinearity and misalignment problems caused by the AENS are addressed to guarantee an improved low-frequency performance. The performance of the prototype is analyzed and validated by experiments. The results have shown that the measurable bandwidth of the prototype is 0.1 Hz ∼ 25 Hz, and the sensitivity is 275 V/(m/s).